Vasopressin Antagonists and Dilutional Hyponatremia - D Mohamed Babatin; Samuel S Lee (Canadian Journal of Gastroenterology)
The paradox of dilutional hyponatremia, as described by Ovid two millennia ago, continues to apply to patients with advanced cirrhosis today: they have unremitting thirst despite vastly increased total body water. Hyponatremia of less than 130 mmol/L occurs in 30% of cirrhotic patients (1), and is mainly due to the reduced capacity of their kidneys to excrete free water.